Synthesis of the first hyperbranched polyorganoethoxysilsesquioxanes and their chemical transformations to functional core–shell nanogel systems. Issue 1 (15th October 2015) - Migulin, Dmitry; Tatarinova, Elena; Meshkov, Ivan; Cherkaev, Georgy; Vasilenko, Natalia; Buzin, Michail; Muzafarov, Aziz
Abstract: Hyperbranched polyvinyl‐ and polymethylethoxysiloxanes were obtained for the first time by heterofunctional polycondensation of the corresponding organoethoxysilanols derived from relevant monosodium organodiethoxysilanolates. Synthesized structures were characterized using 29 Si NMR, 1 H NMR and infrared spectroscopies, gel permeation chromatography and elemental analysis. On the basis of the obtained hyperbranched polyorganoethoxysiloxanes, new 'core–shell' structured polyvinyl‐ and polymethylsilsesquioxanes with adjustable sizes, different crosslinking densities and variable chemical natures of the core–shell surroundings were prepared, investigated and characterized using 1 H NMR and infrared spectroscopies, gel permeation chromatography, thermogravimetric analysis, differential scanning calorimetry and elemental analysis. © 2015 Society of Chemical Industry Abstract : A new route for the preparation of hyperbranched polymethyl‐ and polyvinylalkoxysiloxanes was developed. The obtained hyperbranched polyorganosiloxane structures were further transformed into core–shell structured polyorganosilsesquioxane nanogel particles of two types. Thermal behavior and reactivity of the obtained core–shell structured polyorganosilsesquioxanes with functional vinyl groups, forming in one case an internal core and in the other case an external surface, were studied and compared.